KEWENANGAN MAHKAMAH AGUNG DALAM PEMBENTUKAN DAN PEMBINAAN PENGADILAN MILITER PERTEMPURAN DI INDONESIA (STUDI DI MAHKAMAH AGUNG RI) - Rifandhana, Raditya F. (Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract Journal writing is about The Authority of the Supreme Court stated Article 24, Paragraph 2, the Authority may become Implementation Authority of the Court in the Establishment and Development of the Military Court of Justice Battle .Establishment and Development in Military Courts environment conducted by the Authority of the Supreme Court, the Establishment and Development consists of : a. Establishment of Organization and Development of the High Military Court of Army personnelb. Establishment of Organization and Development of Army personnel Main Military Courtsc. Establishment of Organization and Development of the Military Court Battle Methods used method of empirical research regarding the judicial authority of the Supreme Court in the Establishment and Development of Military Court Battle in Indonesia . Method an empirical approach used juridical system regarding the formation and development of military court battles conducted by the authority of the Supreme Court in cooperation with TNI Commander with a Joint Decree of the Chairman of the Supreme Court of the Republic of Indonesia and the TNI Commander Number: KMA / 065A / SKB / IX / 2004 Number: Skep / 420 / IX / 2004 on Cooperation in Development Coaching Personnel Military For Army personnel on duty at the Court in Environmental Military Court, the include: a. Establishment of Organization and Development of High Military Court of Army personnel b.Establishment of Organization and Development of Army personnel Main Military Court c.Establishment of Organization and Development of Military Court Battle Army personnel. Discussion and results regarding the authority of the Supreme Court stated in Article 24, Paragraph 2, the Authority can be Implementation Authority of the Court in the Establishment and Development of Military Court Battle. Key Words: authority of the supreme court, law effectiveness, organizational formation and development of army personnel in the military courts, a joint decree, military justice Abstrak Penulisan Jurnal ini membahas Kewenangan Mahkamah Agung yang tertera Pasal 24 Ayat 2 Kewenangan tersebut menjadi Pelaksanaan Kewenangan Mahkamah Dalam Pembentukan Dan Pembinaan Pengadilan Militer Pertempuran .Pembentukan dan Pembinaan Peradilan dalam lingkungan Pengadilan Militer dilakukan oleh Kewenangan Mahkamah Agung RI maka Pembentukan dan Pembinaan tersebut terdiri dari: Pembentukan Organisasi dan Pembinaan Prajurit TNI Pengadilan Militer Tinggi Pembentukan Organisasi dan Pembinaan Prajurit TNI Pengadilan Militer Utama Pembentukan Organisasi dan Pembinaan Pengadilan Militer Pertempuran Metode Penelitian digunakan metode penelitian empiris yuridis yang mengenai Kewenangan Mahkamah Agung Dalam Pembentukan dan Pembinaan Pengadilan Militer Pertempuran di Indonesia .Metode Pendekatan digunakan empiris yuridis . Pembentukan dan pembinaan pengadilan militer pertempuran dilakukan oleh kewenangan mahkamah agung yang bekerja sama dengan panglima TNI dengan suatu Surat Keputusan Bersama Ketua Mahkamah Agung Republik Indonesia Dan Panglima TNI Nomor: KMA /065A/SKB/IX/2004 Nomor: Skep/420/IX/2004 Tentang Kerja Sama Dalam Pembinaan Personel Militer Bagi Prajurit TNI Yang Bertugas Pada Pengadilan Dalam Lingkungan Pengadilan Militer , tujuan meliputi : Pembentukan Organisasi dan Pembinaan Prajurit TNI Pengadilan Militer TinggiPembentukan Organisasi dan Pembinaan Prajurit TNI Pengadilan Militer UtamaPembentukan Organisasi dan Pembinaan Prajurit TNI Pengadilan Militer Pertempuran. Pembahasan dan Hasil .Kewenangan Mahkamah Agung tertera pada Pasal 24 Ayat 2 Kewenangan tersebut dapat menjadi Pelaksanaan Kewenangan Mahkamah Dalam Pembentukan Dan Pembinaan Pengadilan Militer Pertempuran. Kata kunci: kewenangan mahkamah agung, efektifitas hukum, pembentukan organisasi dan pembinaan prajurit tni di lingkungan peradilan militer, surat keputusan bersama, peradilan militer